Inguinoscrotal bladder herniation - Is CT a useful tool in diagnosis? (case report) - (:unkn) unknown (ELSEVIER SCIENCE INC, 2002)
Urinary bladder herniation into the inguinal canal is a rare occurrence. The condition is often diagnosed during inguinal hernia surgery. We present a rare case of inguinoscrotal bladder herniation with its computed tomography findings. (C) 2002 Elsevier Science Inc. All rights reserved.
Keywords: bladder; hernia; CT